Alans in Military-Administrative Structures of Great Mongol Empire in 1258—1291 - E. V. Kaziev (Научный диалог, 2023)
The problem of the process of reforming the guards of the Mongolian kaan, which began under the kaan Mongke, continued and ended under the kaan and emperor Kublai is examined in the paper. The purpose of the study is to determine the place of the Alanian military units in the system of the military-administrative organization of the Mongols in the course of this reform. The main material of the study was information from the official “History of the Yuan” and “The Secret History”. In addition, the study used information from the chronicles of Ata Malik Juvaini and Rashid ad-Din, information from the narrative of Guillaume de Rubruk, as well as information from the correspondence of the Alanian princes and Emperor Toghon Temur with Pope Benedict XII. As a result of the study, it was found that the process of reforming the guard took place in several stages, which fell on 1254, 1260, 1262, 1264, 1281 and 1291. It is concluded that over the years the order of recruitment of guards’ units has been changed from patrimonial-aristocratic to territorial. The consequence of this process was the transformation of the guards army of the Mongol kaan into the regular guards army of the Chinese emperor, governed by the order inherent in the Chinese power tradition.